Surgical outcome of Supratentorial Meningioma: A Study of 25 Cases (Journal of Chittagong Medical College Teachers' Association, 2010)
Key words: meningioma; craniotomy; intracranial pressure; CT scan; MRI DOI: 10.3329/jcmcta.v20i1.4934 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):41-44